Anaesthetic and pharmacological techniques to decrease blood loss in liver surgery: a systematic review. Issue 12 (15th June 2015) - Pathak, Samir; Hakeem, Abdul; Pike, Thomas; Toogood, Giles J.; Simpson, Matthew; Prasad, K. Raj; Miskovic, Danilo
Abstract: Background: There is increasing evidence that perioperative blood loss and blood transfusions are associated with poorer short‐ and long‐term outcomes in patients undergoing hepatectomy. The aim of this study was to systematically review the literature for non‐surgical measures to decrease intraoperative blood loss during liver surgery. Methods: The literature search was performed using PubMed, Embase, Cochrane Library, CINAHL and Google Scholar databases. The primary outcome measures were perioperative blood loss and transfusion requirements. A secondary outcome measure was development of ischaemia–reperfusion injury. Results: Seventeen studies met the inclusion criteria and included 1573 patients. All were randomized controlled studies. In eight studies ( n = 894), pharmacological methods, and in another nine studies ( n = 679), anaesthetic methods to decrease blood loss were investigated. Anti‐fibrinolytic drugs, acute normovolaemic haemodilution, autologous blood donation and use of inhalational anaesthetic agent may affect blood loss and post‐operative hepatic function. Conclusions: There is potential for use of non‐surgical techniques to decrease perioperative bleeding. However, on the basis of this review alone, due to heterogeneity of randomized trials conducted, no particular strategy can be recommended. Future studies should be conducted looking at pathways to decrease bleeding in liver surgery.